Peran Otomatisasi dan Robotika dalam Era Digital: Trasformasi Bisnis Melalui Otomatisasi dan Robotika dalam Era Digital - Huda, Miftachul; Sri Pudjiarti, Emiliana (Universitas 17 Agustus 1945 Semarang, 2024)
This paper explores the role of automation and robotics in the ongoing digital era that has brought about fundamental changes in the global business paradigm. Automation and robotics are two major forces coming to the fore in this change. This article explores the role of automation and robotics in the digital era, with a focus on ongoing business transformation. Automation and robotics have opened doors for companies to improve their operational efficiency. Along with that, companies also gain the potential to improve the quality of their products and services. Business transformation through automation and robotics is no longer just an option, but a necessity to compete in an increasingly competitive market. However, while the benefits are clear, there are strategic challenges that need to be faced in implementing automation and robotics. Cost management, system integration, and data security are some of these challenges.